The Logic of Argumentation of Mathematics Teacher Professional Education Students in a Case Study of Learning - I Made Dharma Atmaja; Kadek Rahayu Puspadewi (Universitas Pendidikan Ganesha, 2026)
Mathematics Teacher Professional Education (PPG) students often experience difficulties in transforming teaching experiences into logical, evidence-based pedagogical arguments. The gap between the demands of analytical, reflective practice and argumentation skills that tend to be narrative-intuitive is a crucial problem that hinders the development of teacher professionalism. Therefore, this study aims to analyze in depth the logical structure of argumentation constructed by students in narrative case studies of learning problem solving. This study uses a qualitative approach with a multi-case study design to explore the phenomenon holistically. The research subjects were 10 PPG Mathematics students. Data were collected through documentation techniques, with the main instrument being 10 case study narrative documents compiled by each subject. Data analysis was conducted using thematic content analysis that focused on the decomposition of arguments into premises (problems), interventions (solutions), and conclusions (evidence). The analysis results identified two dominant argumentation patterns: Coherent Argumentation, which shows a strong causal relationship between a specific problem, a relevant solution, and verified evidence. Partial argumentation is characterized by general claims without strong supporting data. It is concluded that the ability to construct coherent and evidence-based arguments is a fundamental competency that differentiates the quality of students' pedagogical reflection, addressing the main problem regarding the gap in argumentation skills.